The Effectiveness of School Instagram Application in Guidance and Counseling Services at SMA Negeri 11 Takengon (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to determine the effectiveness of using a school Instagram application as a medium for guidance and counseling services at SMA Negeri 11 Takengon. The background of this research is based on the rapid development of information and communication technology, which encourages schools to utilize social media as a supporting tool in educational services, particularly guidance and counseling. The research method used is a quantitative approach with a descriptive research design. The subjects of this research are students of SMA Negeri 11 Takengon who actively follow the school’s Instagram account. Data were collected through questionnaires developed based on indicators of the effectiveness of guidance and counseling services, including aspects of understanding, interest, accessibility, and service benefits. The collected data were analyzed using descriptive statistical techniques. The results show that the use of the school Instagram application is categorized as effective in supporting guidance and counseling services. Students find it easier to access information, better understand counseling materials, and show greater interest in participating in services delivered through Instagram. Therefore, Instagram can be considered an innovative and relevant alternative medium for implementing guidance and counseling services in schools.